Physiological responses of eight maize varieties to salinity under the field and greenhouse conditions (Bangladesh Journal of Botany, 2019)
An experiment was conducted in two fields (normal and saline) to study the effect of salinity on eight varieties of maize (Zea mays L.) for three years. Another experiment was carried out in three salinity levels, zero (control), 50 and 100 mM NaCl in greenhouse at the factorial design in a year. During the experiment characters such as chlorophyll a, chlorophyll b and proline content were measured. Comparison of means in different soil of salinity showed that, there were significant differences in genotypes in most traits. Maximum amount of chlorophyll a was observed in S.C704 in control condition and there was no significant difference from B73. In field condition maximum and minimum amount of proline were observed in S.C704 in saline condition and K3615/1 in normal condition, respectively. In greenhouse, maximum amount of chlorophyll a was observed in K3615/1 variety.